2013
DOI: 10.1111/ejed.12020
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ICT in Education: a survey of schools in Europe

Abstract: The Survey of Schools: ICT in education commissioned in 2011 by the European Commission took place between January 2011 and November 2012, with data collection in autumn 2011. This article presents the main findings of the Survey based on over 190,000 questionnaire answers from students, teachers and head teachers in primary, lower and upper secondary schools randomly sampled. The article details the analytical framework design and the survey methodology implemented. It then presents the main ‘state of the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
163
2
47

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(239 citation statements)
references
References 7 publications
9
163
2
47
Order By: Relevance
“…Throughout recent years, attempts have also been made in discussing pedagogical aspects of digital competence from a contextual perspective (From 2017;Wastiau et al 2013;Vanderlinde and van Braak 2010). From (2017) argued, for example, that the pedagogical aspects of digital competence should not only be regarded as a separate set of skills and competences embedded at the level of teachers but also be embedded within and across the wider school organization.…”
Section: Towards Pedagogical Aspects Of Digital Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Throughout recent years, attempts have also been made in discussing pedagogical aspects of digital competence from a contextual perspective (From 2017;Wastiau et al 2013;Vanderlinde and van Braak 2010). From (2017) argued, for example, that the pedagogical aspects of digital competence should not only be regarded as a separate set of skills and competences embedded at the level of teachers but also be embedded within and across the wider school organization.…”
Section: Towards Pedagogical Aspects Of Digital Competencementioning
confidence: 99%
“…In the same line of reasoning, Vanderlinde and van Braak (2010) put forth the importance of supportive organizational infrastructures, formation of policy-related documents and a strategic leadership that can support teachers in transforming policies into realistic goals while teachers can put these goals into action in the everyday teaching practice. Also Wastiau et al (2013) argued for a comprehensive organization of policies, leadership and supportive organizational infrastructures when trying to achieve technology integration and development of the digital competences needed.…”
Section: Towards Pedagogical Aspects Of Digital Competencementioning
confidence: 99%
“…One macro-level survey of schools focused on ICT in education was cnducted by the European Commission in the years 2011-2012 with over 190,000 students, teachers and principals. This study introduced concepts of digitally supportive schools and digitally confident and supportive teachers (Wastiau, Blamire, Kearney, Quittre, Van de Gaer & Monseur 2013). However, according to , teachers select applications of technology in line with their selection of other curricular variables and processes that fit into their existing beliefs about "good" education and about the nature of their roles as teachers.…”
Section: 1mentioning
confidence: 99%
“…This learning process has a self-evident character and takes place in the daily working situation [2]. It is seen as the development of the individual through interaction with others [3]. Digital learning often happens spontaneously and unconsciously without any a priori stated objectives in terms of learning outcomes [1].…”
Section: Introductionmentioning
confidence: 99%
“…Wastiau et al [3] have also indicated that students have the highest frequency of digital learning technology use when taught by teachers who possess appropriate digital skills, who use the internet, including social media [9].…”
Section: Introductionmentioning
confidence: 99%